Caribbean Agriculture: Strategic Responses to Trade Liberalization and Globalization - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
T Josling and C Y Thomas. Caribbean Agro-economic Society, University of the West Indies, and CTA co-publication. 1998. 65 pp.ISBN 976 620 122 6Fax: + 1 876 662 92 38Email: mainlib@library.uwi.tt